The effects of cannabidiol via TRPV2 channel in chronic myeloid leukemia cells and its combination with imatinib. Issue 4 (4th March 2022) - Maggi, Federica; Morelli, Maria Beatrice; Tomassoni, Daniele; Marinelli, Oliviero; Aguzzi, Cristina; Zeppa, Laura; Nabissi, Massimo; Santoni, Giorgio; Amantini, Consuelo
Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative disorder characterized by accumulation of immature cells in bone marrow and peripheral blood. Although successful results were obtained with tyrosine kinase inhibitors, several patients showed resistance. For this reason, the identification of new strategies and therapeutic biomarkers represents an attractive goal. The role of transient receptor potential (TRP) ion channels as possible drug targets has been elucidated in different types of cancer. Among natural compounds known to activate TRPs, cannabidiol (CBD) displays anticancer properties. By using FACS analysis, confocal microscopy, gene silencing, and cell growth assay, we demonstrated that CBD, through TRPV2, inhibits cell proliferation and cell cycle in CML cells. It promoted mitochondria dysfunction and mitophagy as shown by mitochondrial mass reduction and up‐regulation of several mitophagy markers. These effects were associated with changes in the expression of octamer‐binding transcription factor 4 and PU.1 markers regulated during cellular differentiation. Interestingly, a synergistic effect by combining CBD with the standard drug imatinib was found and imatinib‐resistant cells remain susceptible to CBD effects. Therefore, the targeting of TRPV2 by using CBD, through the activation of mitophagy and the reduction in stemness, could be a promising strategy to enhance conventional therapy and improve the prognosis of CML patients. Abstract : Our data showed that cannabidiol, via TRPV2, induces cell proliferation blockage, mitophagy, and changes in the expression of differentiation markers in chronic myeloid leukemia cells. Cannabidiol acts synergistically with imatinib and it also reduces cell viability of imatinib‐resistant cells.